Análise experimental e modelagem da permeação de hidrogênio em membranas de paládio e de paládio-prata - Arzani, Fernanda Aparecida (2018)
Hydrogen has stood out for the generation of clean energy. Its application in fuel cells produces water as a residue but requires high purity. The main way to obtain hydrogen is the steam reforming of methane, a process in which other compounds are also produced and need to be separated. Membrane separation processes can be used and palladium (Pd) membranes are an option due to their high permeability and selectivity to hydrogen. The use of thin metallic layers on porous substrates and a mixture of palladium with silver (Ag) allow an increase in the flow of hydrogen through the membrane. Having this in mind, this work aimed to analyze the formation of Pd and Pd-Ag membranes on alumina support and to evaluate their permeability and selectivity to hydrogen. Therefore, electrochemical depositions were made on alumina hollow fibers under different reaction conditions. The membranes were tested at temperatures of 300 to 450 ºC under pressures of 40 to 200 kPa. A palladium composite membrane was obtained, which presented a hydrogen flow of 0.389 mol.m-2.s-1 and a selectivity of 35 in relation to nitrogen. A Pd-Ag membrane with infinite selectivity and a hydrogen flow of 0.204 mol.m-2.s-1 was also obtained. Some membranes produced showed defects in the metallic layer, so they were not selective to hydrogen due to difficulties in the simultaneous deposition of palladium and silver added to defects on the surface of the support. To understand the permeation of hydrogen in palladium composite membranes supported on a porous substrate, a mathematical model was presented. Starting from the model of Ward and Dao (1999) and adding a diffusion model in porous media, based on the flows of Knudsen and Poiseuille, hydrogen permeated in composite membranes were simulated. Simulated flows were compared to values obtained experimentally. At 450 ºC, the best approximation between the simulated and experimental values was obtained, with the calculated values being 55% higher than the experimental values.